Between Landscape and the Screen: Locative Media, Transitive Reading, and Environmental Storytelling - Jill Didur; Lai-Tze Fan (Media Theory)
In what ways can the everyday citizen encourage sustainability and promote biodiversity in spaces that are as fragmented, industrial, and toxic as the city? This paper investigates how GPS-enabled platforms afford user experiences of what we call â€œembodied knowingâ€ â€“ learning through encounter, awareness through physicality â€“ in urban wilds, which represent informal greenspaces on the edges of urban development. The locative mobile application that we have produced, Global Urban Wilds, complicates notions of time, space, and preservation in ruderal landscapes that survive in city spaces, demonstrating that they come into tension with layers of biodiversity, technological development, and settler culture in urban contexts such as MontrÃ©al, Canada. As such, we show how the appâ€™s mediation of these layers through a method of transitive reading promotes a userâ€™s critical negotiation and awareness of urban ecosystems in relation to todayâ€™s â€œsmartâ€ city.